PENGARUH KUALITAS PELAYANAN CUSTOMER SERVICE TERHADAP LOYALITAS PELANGGAN PADA TOKO NIBRAS HOUSE BEKASI - Novia, Reni; Munjiarti, Mumun (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2024)
This study aims to determine the effect of customer service quality on customer loyalty. The data collection method used is a questionnaire. The population in this study is customers of Toko Nibras House Bekasi who have customer membership status (membership) and have made product purchases in 2022. The sampling technique used was purposive sampling with a sample of 64 respondents. The data analysis methods used are validity tests, reliability tests, normality tests, linearity tests, simple linear regression analysis, and partial significance tests (T) using the SPSS 26 application. The results of this study showed that t-count > t-table (8.510 > 1.669). From the results of the t test, a significance value is also obtained smaller than 5% or 0.05 (0.000 < 0.05) so that it can be concluded that the quality of customer service has a positive and significant effect on customer loyalty at Nibras House Bekasi Store. Keywords : Service Quality, Customer Service, Customer Loyalty, Customer Perception, Customer Expectations